ASSESSMENT OF RADIATION EXPOSURE LEVEL IN BLACKSMITHING WORKSHOP IN GOMBE, GOMBE STATE - Olanrewaju, Abiodun; AbdulKareem , Nurudeen Mohammed; Raheem, Isiaka O. (FUDMA JOURNAL OF SCIENCES, 2021)
Measurement of terrestrial background ionizing radiation of blacksmith workshops of Gombe State, Nigeria was carried out using well-calibrated Geiger-Muller counter meters and a meter tape. The measured average exposure rate of two line-sections are 0.018Â±0.002 and 0.017Â±0.002 mRh-1. Estimated equivalent dose rates for the two line-sections are 1.50 and 1.45 mSvy-1. The average absorbed dose rates estimated in line-section one and line-section two are 154.94 and 149.97 nGyh-1 respectively. Annual effective dose equivalent (AEDE) of 0.48 mSvy-1 was obtained for outdoor exposure in line-section one while in line-section two, AEDE was 0.23 mSvy-1. The calculated mean excess lifetime cancer risk values for the blacksmith workshop sections are 0.83x 10-3 and 0.80 x 10-3. The obtained values for background ionizing radiation in the line-sections of blacksmith workshop were above the recommended standard limit by ICRP while the absorbed doses (D) were above the recommended value and AEDE calculated in two line-sections of blacksmithing workshops were within the safe values this implies that blacksmithing activities in these areas may not influence the doses received by public. The excess lifetime cancer risk (ELCR) estimated were higher than their world permissible values of 0.29 x 10-3 respectively. The calculated dose to organs showed that the testes have the highest organ dose of 0.153 mSvy-1while liver has the lowest organ dose of 0.086 mSvy-1. This result shows that exposure to